2023
DOI: 10.1002/lpor.202300517
|View full text |Cite
|
Sign up to set email alerts
|

Novel Red Mechanoluminescence in Mn‐Doped ZnGa2S4 Crystal Phosphors via a Molten Salt Shielding Method

Abstract: Owing to their unique characteristic of direct mechanical‐to‐optical energy conversion, mechanoluminescence (ML) crystals have drawn considerable interest for visible stress sensing, flexible and stretchable displays, and advanced anti‐counterfeiting. However, among the visible emissions of synthetic ML materials, high‐performance red‐emission semiconductors with ideal color‐rendering indices are relatively scarce, which restricts their future applications. In this work, red ML emission with CIE coordinates (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…MSS can effectively control the growth of particles and crystallization of materials and avoid particle agglomeration occurring during SSR. Moreover, researchers have developed new MSS-based preparation methods, such as the molten salt shielding method and coprecipitation/molten salt two-step synthesis method, which can prepare sulfides and oxysulfides, , nonoxide ceramics, oxide nanoparticles, etc. Reports on synthesis of ternary layer tantalates by MSS mainly include Cu 5 Ta 11 O 30 and Cu 3 Ta 7 O 19 with CuCl flux, , Pb 1.5 Ta 7 O 19 , PbTa 4 O 11 , and Pb 3 Ta 4 O 13 with Na 2 SO 4 , K 2 SO 4 , and PbCl 2 flux, , and Na 2 Ta 4 O 11 with Na 2 SO 4 and K 2 SO 4 flux .…”
Section: Introductionmentioning
confidence: 99%
“…MSS can effectively control the growth of particles and crystallization of materials and avoid particle agglomeration occurring during SSR. Moreover, researchers have developed new MSS-based preparation methods, such as the molten salt shielding method and coprecipitation/molten salt two-step synthesis method, which can prepare sulfides and oxysulfides, , nonoxide ceramics, oxide nanoparticles, etc. Reports on synthesis of ternary layer tantalates by MSS mainly include Cu 5 Ta 11 O 30 and Cu 3 Ta 7 O 19 with CuCl flux, , Pb 1.5 Ta 7 O 19 , PbTa 4 O 11 , and Pb 3 Ta 4 O 13 with Na 2 SO 4 , K 2 SO 4 , and PbCl 2 flux, , and Na 2 Ta 4 O 11 with Na 2 SO 4 and K 2 SO 4 flux .…”
Section: Introductionmentioning
confidence: 99%
“…At a relatively low force, the ML may be ascribed to the triboelectric effect. The increase of applied forces would distort the host lattice and raise the piezoelectric potential of the host dramatically, resulting in a rapid enhancement of the ML intensity (Figures S8 and S9; Table S1). It was reported that piezoelectricity in noncentrosymmetric structures is significantly stronger than triboelectricity, , and the distortion index in the hexagonal phase is indeed much higher than that in the cubic phase (Table S2). Figure g shows the ML repeatability of the samples.…”
mentioning
confidence: 98%